Explaining the Great Moderation exchange rate volatility puzzle - Vania Stavrakeva; Jenny Tang (Federal Reserve Bank of Boston, 2024)
In this paper, we study how the volatility of both realized and expected macroeconomic variables relates to the variation in exchange rate volatility through the prism of the Great Moderation hypothesis. We find significant heterogeneity in exchange rate trend volatility across currency pairs despite decreases in the volatility of expected future interest rate differentials and of realized yields themselves. We argue that time variation in the relationship between macroeconomic variables and exchange rates has prevented the Great Moderation in realized yield volatility from translating to a decrease in exchange rate volatility. Considering a Campbell-Shiller-type decomposition of exchange rate changes into forward-looking components linked to inflation, policy rate, and currency risk premia expectations, we find that the Great Moderation in volatility of expected yield differentials cannot explain the patterns in exchange rate volatility we observe. The main drivers of these patterns were trends in the volatility of the currency risk premium component and in the covariance between the components capturing the strength of the Fama puzzle and the expected responsiveness of monetary policy to inflation.
Keywords: E44; F31; G15; 330; Exchange rates; international finance; volatility trends; risk premia; Fama puzzle